DESIGN AND OPTIMIZATION OF INVOLUTE MODEL DURING THE DESIGN OF THE REORGANIZATION PLAN OF THE RAILWAY LINE - Korzhenevych, I. P. (Science and Transport Progress, 2007)
Construction of models for existing and design positions of the plan of a railway in a method of evolvents and optimization of the design decision is considered.